Genetic diversity analysis and character associations in black cumin (Nigella sativa L.) based on agro-morphological and phytochemical traits. Issue 9 (29th July 2019) - Gholizade, Amir; Sharifi Olounabadi, Ahmad Reza; Hosseini, Seyed Morteza; Sharifi, Hossein
ABSTRACT: Black cumin ( Nigella sativa L.) is one of the important medicinal plants that used in food and pharmaceutical industries. In the present study, 32 Iran endemic black cumin genotypes were evaluated through randomized complete block design with three replications in 2016 and 2017 growing seasons to determine the extent of genetic diversity and character associations for agro-morphological and phytochemical traits. Results showed the significant differences between genotypes for all traits studied. Clustering analysis using agro-morphological and phytochemical traits grouped genotypes into the two distinct groups. The values of percentage of essential oil and fatty oil content varied from 0.65 to 0.1.36% and 25.30% to 35.02% between genotypes, respectively. The highest seed yield and fatty oil yield obtained for Arak genotype. GC and GC/MS analyses of essential oil and fatty oil compositions of the Arak genotype revealed that p -cymene and linoleic acid were main components, respectively. Stepwise regression analysis revealed that shoot dry mass, days to ripening and seed length were the most important traits associated with seed yield, fatty oil yield and essential oil yield. Hence, these traits can be considered as important indicators for early selection for seed yield and quality in black cumin breeding programs.